Heterogeneous mechanical hyperelastic behavior in the porcine annulus fibrosus explained by fiber orientation: An experimental and numerical approach. (April 2020) - Dusfour, G.; LeFloc'h, S.; Cañadas, P.; Ambard, D.
Abstract: Our aim is to estimate regional mechanical properties of the annulus fibrosus (AF) using a multi-relaxation tensile test and to examine the relevance of using the transverse dilatations in the identification procedure. We collected twenty traction specimens from both outer (n = 10) and inner (n = 10) sites of the anterior quadrant of the annulus fibrosus of one pig spine. A 1-h multi-relaxation tensile test in the circumferential direction allowed us to measure the force in the direction of traction and the dilatations in all three directions. We performed a specific-sample finite element inverse analysis to identify variations, along the radial position, of material and structural parameters of a hyperelastic compressible and anisotropic constitutive law. Our experimental results reveal that the outer sites are subjected to a significantly greater stress than the inner sites and that both sites exhibit an auxetic behavior. Our numerical results suggest that the inhomogeneous behavior arises from significant variations of the fiber angle taken into account within the hyperelastic constitutive law. In addition, we found that the use of the measured transverse dilatations in the identification procedure had a strong impact on the identified mechanical parameters. This pilot study suggests that, in quasi-static conditions, the annulus fibrosus may be modeled by a hyperelastic compressible and anisotropic law with a fiber angle gradient from inner to outer periphery. Graphical abstract: Image 1